Kinematic and dynamic fault slip analyses: Implications from the surface rupture of the 2023 Elbistan (Kahramanmaras) (Mw7.6) earthquake, Turkiye - Kokum, Mehmet (Pergamon-Elsevier Science Ltd, 2024)
On 6 February 2023, the Elbistan (Kahramanmaras,) (Mw7.6) earthquake produced a strike-slip type coseismic surface rupture zone, involving the sinistral slip of the Dogansehir Fault (DF) and Cardak Fault (CF). Fault slickenlines and seismic slickenlines were included in the inversion as part of the dynamic analysis. The inversion of fault slickenlines collected from nine outcrops along the surface rupture following the earthquake, many of which developed during the event and are referred to as coseismic slickenlines, reveals a strike-slip stress regime (sigma(2) = sigma(v)) characterized by a NE-SW (mean azimuth: N045 degrees E) sigma(1) (maximum) axis. Relict slip planes adjacent to main slip surfaces were found to host slickenlines that appear much older than the most recent earthquake, referred to as paleoslip slickenlines. Inversion of the paleoslip slickenline collected from four outcrops reveals an extensional stress regime (sigma(1) = sigma(v)) characterized by a NE-SW sigma(3) (min) axis, consistent with previously published studies. To define a significant stress tensor concerning present-day faulting within the investigated area, the inversion method was applied to the seismic slickenlines of shallow earthquakes in the surface rupture area. The inversion of sixty selected nodal planes reveals a strike-slip stress regime (sigma(2) = sigma(v)) characterized by an NNE-SSW (N10 degrees E) sigma(1) (max) axis. Besides, the moment tensor summation analysis using displacement vectors inferred from visible field markers offset during the earthquake was applied to the seismic slickenlines as part of the kinematic analysis. The shortening and extension results for the moment tensor summation are 044/36 and 307/11 indicating NE-SW compression. Results of the moment tensor summation (weighted by fault displacement) agree broadly with the inversion of seismic slickenlines results, indicating an NE orientation for shortening and an SE orientation for extension.
Keywords: Coseismic; Earthquake; Inversion; Slickenline; Surface rupture